Job Mission as a Substitute for Monetary Incentives: Benefits and Limits - Cassar, Lea (Management Science, 2019)
Many jobs are connected to a prosocial mission—namely, to a social purpose beyond profit maximization. I use three laboratory experiments to investigate if employers can use the mission to economize on monetary incentives. In my first experiment, I exogenously vary whether the agents’ effort generates a donation to a charity of their choice (matched mission), generates a donation to a charity chosen by another subject (random mission), or generates no donation (no mission). I find that the mission, whether matched or random, increases effort compared to the no-mission condition. Consistent with the theory, nonmotivated principals exploit the agents’ motivation by offering lower piece rates, whereas very motivated principals pay higher piece rates to boost the donation. I find no difference in the effort and piece rate between the matched- and random-mission conditions. In my second experiment, I use a selected pool of motivated subjects but still observe no difference between these two treatments. In my third experiment, I explore whether the effect of mission-matching may arise through gift exchange: principals decide between choosing the mission or delegating the choice to the agent. I do not find evidence that agents who are delegated the mission choice reciprocate with higher effort. These findings suggest that while a prosocial mission allows for economizing on monetary incentives, there are no further gains from increasing the quality of the mission-matching. Data and the supplemental material are available at https://doi.org/10.1287/mnsc.2017.2903 . This paper was accepted by Uri Gneezy, behavioral economics.